Noah Webster and the standardization of sound - Elaina FRULLA (E-REA)
Early American writers believed that what they understood as “standard” English was necessary for the functioning and maintenance of the newly established nation. As a result, “standard” English was placed upon a metaphorical pedestal that “accent,” whether regional (within the nation) or foreign, threatened to knock over. This chapter examines Noah Webster’s project to standardize speech, particularly his call for pronunciation based on a “principle of analogy.” The chapter also examines the obstacles Webster faced during his mission to develop a national language, which included overcoming regional vocal differences and halting what he perceived as the corruptive influence of foreign languages. After reviewing scholarship on the history of American English as well as scholarship on Webster’s work, I argue that Webster wanted to standardize not only spelling but also, and more importantly, the sounds associated with the letters of the English alphabet. If, according to Webster, Americans could overcome the desire to imitate “corrupt” English and foreign models of the pronunciation of various sounds attached to letters, then a standardized pronunciation could be achieved.